(untitled) (Italian Journal of Public Health, 2011)
We report two cases of severe malaria who presented with non-specific clinical features. One of the cases is a 50 year old female who was brought to our hospital with high grade fever and severe abdominal pain, whereas the other case was a 20 year old male presented with high grade fever and headache. Both the cases presented with abnormal liver and renal function tests. P.malariae and P.falciparum are responsible for clinically important renal disease the former causes chronic progressive syndrome and the latter causes acute renal disease. Severe malaria may present with non specific clinical features making it difficult to distinguish from other febrile illness.